FAM19A5, a brain-specific chemokine, inhibits RANKL-induced osteoclast formation through formyl peptide receptor 2. Issue 1 (December 2017) - Park, Min; Kim, Hyung; Lee, Mingyu; Park, Byunghyun; Lee, Ha; Cho, Eun; Seong, Jae; Bae, Yoe-Sik
Abstract Osteoclasts can be differentiated from bone marrow-derived macrophages (BMDM). They play a key role in bone resorption. Identifying novel molecules that can regulate osteoclastogenesis has been an important issue. In this study, we found that FAM19A5, a neurokine or brain-specific chemokine, strongly stimulated mouse BMDM, resulting in chemotactic migration and inhibition of RANKL-induced osteoclastogenesis. Expression levels of osteoclast-related genes such asRANK, TRAF6, OSCAR, TRAP, Blimp1, c-fos, andNFATc1 were markedly decreased by FAM19A5. However, negative regulators of osteoclastogenesis such asMafB andIRF-8 were upregulated by FAM19A5. FAM19A5 also downregulated expression levels of RANKL-induced fusogenic genes such asOC-STAMP, DC-STAMP, andAtp6v0d2 . FAM19A5-induced inhibitory effect on osteoclastogenesis was significantly reversed by a formyl peptide receptor (FPR) 2 antagonist WRW4 or by FPR2-deficiency, suggesting a crucial role of FPR2 in the regulation of osteoclastogenesis. Collectively, our results suggest that FAM19A5 and its target receptor FPR2 can act as novel endogenous ligand/receptor to negatively regulate osteoclastogenesis. They might be regarded as potential targets to control osteoclast formation and bone disorders.